1999
DOI: 10.1111/j.1530-0277.1999.tb04537.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Serum Des‐gamma‐Carboxy Prothrombin in Alcoholic Liver Disease Without Hepatocellular Carcinoma

Abstract: The purpose of this study is to determine serum des-gamma-carboxy prothrombin (DCP) levels in benign liver diseases by a new sensitive method, and to demonstrate the elevation of serum DCP in alcoholic liver disease (ALD) without hepatocellular carcinoma (HCC). Median values of serum DCP were 16.2 mAU/ml (range: 3.2 to 1570 mAU/ml) in ALD and 16.7 mAU/ml (1.2 to 75.4 mAU/ml) in viral liver disease (VLD). Using the cut-off value of 40 mAU/ml as a tumor marker for HCC, 21% (11/52) was positive in ALD and 2% (1/5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…34 Another caveat is that PIVKA-II may simply reflect liver dysfunction, because raised levels in the absence of demonstrable vitamin K deficiency are occasionally found in adults with chronic liver disease. [42][43][44][45] Our results argue strongly against either possibility because in 15/18 infants, the initially raised PIVKA-II declined after the administration of vitamin K at rates consistent with previous estimates of the plasma disappearance of PIVKA-II. 34 46 The wide range of but low median serum K 1 concentrations after oral administration of Konakion MM is clear evidence of a variable and often low efficiency of intestinal absorption in infants with cholestasis.…”
Section: Discussionsupporting
confidence: 81%
“…34 Another caveat is that PIVKA-II may simply reflect liver dysfunction, because raised levels in the absence of demonstrable vitamin K deficiency are occasionally found in adults with chronic liver disease. [42][43][44][45] Our results argue strongly against either possibility because in 15/18 infants, the initially raised PIVKA-II declined after the administration of vitamin K at rates consistent with previous estimates of the plasma disappearance of PIVKA-II. 34 46 The wide range of but low median serum K 1 concentrations after oral administration of Konakion MM is clear evidence of a variable and often low efficiency of intestinal absorption in infants with cholestasis.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies revealed that DCP is not only found in the HCC tissues, but also in the non-cancer tissues surrounding HCC and even in some benign liver diseases, such as acute hepatitis and chronic hepatitis [20,23,24]. These observations imply the complicated causes and mechanisms of DCP production.…”
Section: The Causes and Mechanisms Of Dcp Productionmentioning
confidence: 99%
“…The background liver showed cirrhosis (a). The nodule showed a slightly increased cell density and sinusoidal dilatation in comparison to the background liver tissue (b) the elevation of PIVKA II has not been clarified [6]. Ethanol intake and the following vitamin K deficiency may act, in part, due to an increased serum PIVKA II level in alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 97%